Performance of Floating Raft Fertigation System on Water Spinach Plants (Ipomea reptans Poir.) Cultivation - Rizal Hadyan Fadhlillah; Sophia Dwiratna; Kharistya Amaru (Talenta Publisher, 2019)
The increase of human population impact to more land needed for residence and has an impact on the decreasing land for agriculture, especially in urban areas. One of solution for farming in urban areas is by utilizing rooftop farming by hydroponic cultivation. The hydroponic system that used in this research is floating raft system. This study aims to determine the performance of the floating raft fertigation system which includes the amount of energy consumption, water, nutrient solution, growth uniformity and yield productivity in water spinach cultivation using floating raft fertigation system for one period of growth. This research was carried out on the rooftop of the building of the Food Industry Technology Department of Padjadjaran University with descriptive analysis method. The parameters measured in this study were the amount of water consumption, nutrition and electrical energy from the floating raft fertigation system that was used and uniformity of the results of plant growth including plant height, root length and plant weight at harvest determined in this study, 16 days after transplanting. Result showed that water consumption for one time growth period water spinach was 300,63 liters; consumption of nutrients was 3860 ml and electricity consumption was 31,816 kW. The uniformity of water spinach plant results of the study was in the category of good. The efficiency of water use was 99.6 kg/m3 and plant productivity based on research results is 72.8 kg/m2.